A Novel Traveling Wave Based Differential Protection for Distributed Parameter Line - Baina He; Yunwei Zhao; Hengxu Ha (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Traditional current differential protection is based on Kirchhoff’s Law, certainly is severely influenced by the distributed capacitance current. A new traveling wave based differential protective principle is proposed by employing the characteristics of current traveling waves for the distributed parameter line model. There are fixed propagation relations between traveling waves of terminals as the line is healthy or the fault is external, however, the relationship is broken for the internal faults. The protective criterion and scheme are established by this character. The key technique is to quickly calculate the propagating traveling waves from the other terminal on line. The coefficients of propagation function from one terminal to another are obtained by using orthogonal projection methods. The principle and algorithm need not high sampling frequency, are adaptive for not only fundamental component but the transient components, as well as is not sensitive to setting parameters. The large amounts of ATP simulation tests show that the protective scheme and algorithm is simple with high reliability, security, speedy and sensitivity. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3254